2019
DOI: 10.1002/adhm.201900035
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Imaging of Vaccine Biodistribution Using Zwitterionic NIR Nanoparticles

Abstract: Efficient and timely delivery of vaccine antigens to the secondary lymphoid tissue is crucial to induce protective immune responses by vaccination. However, determining the longitudinal biodistribution of injected vaccines in the body has been a challenge. Here, the near‐infrared (NIR) fluorescence imaging is reported that can efficiently enable the trafficking and biodistribution of vaccines in real time. Zwitterionic NIR fluorophores are conjugated on the surface of model vaccines and tracked the fate of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…One important factor is localization of antigens in lymphoid tissues following immunization. Numerous preclinical studies have found that nanoparticles of a variety of compositions drain efficiently through the lymph, but upon reaching secondary lymphoid tissues remain primarily localized within the subcapsular sinus and the medulla or are seemingly excluded from B cell follicles (Katagiri et al, 2019;Manolova et al, 2008;Moon et al, 2012;Mueller et al, 2015;Reddy et al, 2006;Shukla et al, 2017;Wang et al, 2019). Since interactions with B cells within follicles are essential for the development of high-affinity antibodies, localization of antigen within these regions has the potential to drive more robust humoral responses.…”
Section: Introductionmentioning
confidence: 99%
“…One important factor is localization of antigens in lymphoid tissues following immunization. Numerous preclinical studies have found that nanoparticles of a variety of compositions drain efficiently through the lymph, but upon reaching secondary lymphoid tissues remain primarily localized within the subcapsular sinus and the medulla or are seemingly excluded from B cell follicles (Katagiri et al, 2019;Manolova et al, 2008;Moon et al, 2012;Mueller et al, 2015;Reddy et al, 2006;Shukla et al, 2017;Wang et al, 2019). Since interactions with B cells within follicles are essential for the development of high-affinity antibodies, localization of antigen within these regions has the potential to drive more robust humoral responses.…”
Section: Introductionmentioning
confidence: 99%
“…65 Katagiri et al reported a real-time trafficking method of a model vaccine labeled with zwitterionic NIR fluorophore ZW800-1C, which enabled the determination of the longitudinal fate of vaccines after intradermal administration (figure 2D). 66 Of note, zwitterionic NIR fluorophores show minimal interactions with biological tissues and do not interfere with the interactions between vaccines and immune cells due to their non-sticky properties resulting from their balanced charges and hydrophilicity. [67][68][69][70][71][72] This combination of zwitterionic NIR fluorophores and NIR imaging can be useful for the optimization of vaccine design as well as the safety evaluation of clinical vaccine candidates.…”
Section: "Ex Vivo" Labeling For Immune Cellsmentioning
confidence: 99%
“…Another study which demonstrates the versatility of NIRF imaging as well as the significance of imaging in development and evaluation of a vaccine was carried out by Katagiri et al (2019). This group conjugated a zwitterionic NIR fluorophore, ZW800-1C, on the surface of OVA (OVA-ZW), and subsequently conjugated this to silica nanoparticles of 20 nm (SiNP-20 nm) and 100 nm (SiNP-100 nm) in diameter to form what are referred to as ONP1 and ONP2, respectively.…”
Section: Near Infrared Fluorescence Imagingmentioning
confidence: 99%
“…The nanovaccine was then evaluated for in vivo biodistribution (Katagiri et al, 2019). Mice were divided into three groups depending on the vaccine formulation they received: ONP1, ONP2, and free OVA-ZW.…”
Section: Near Infrared Fluorescence Imagingmentioning
confidence: 99%
See 1 more Smart Citation